2009
DOI: 10.1053/j.gastro.2009.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Physiology, Injury, and Recovery of Interstitial Cells of Cajal: Basic and Clinical Science

Abstract: In the last 15 years, our understanding of the cellular basis of gastrointestinal function has been altered irreversibly by the discovery that normal gastrointestinal motility requires interstitial cells of Cajal (ICC). Research in this relatively short time period has modified our original concept that the core unit that controls motility is made up of nerves and smooth muscle, to one that now includes ICC. This concept has now expanded to beyond the gastrointestinal tract, suggesting that it may be a fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 76 publications
(78 reference statements)
4
147
0
Order By: Relevance
“…Contemporarily, physiologists were able to attribute to them the role of pacemakers for gut peristalsis, being able to generate slow waves (13,(16)(17)(18). Indeed, a combination of morphological and functional investigations was also able to demonstrate that the ICC play a role of intermediate in neurotransmission (12,(17)(18)(19). Another function attributed to some ICC populations is that of being part of the 'stretch receptor'.…”
Section: Interstitial Cells Of Cajal (Icc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporarily, physiologists were able to attribute to them the role of pacemakers for gut peristalsis, being able to generate slow waves (13,(16)(17)(18). Indeed, a combination of morphological and functional investigations was also able to demonstrate that the ICC play a role of intermediate in neurotransmission (12,(17)(18)(19). Another function attributed to some ICC populations is that of being part of the 'stretch receptor'.…”
Section: Interstitial Cells Of Cajal (Icc)mentioning
confidence: 99%
“…Interestingly, by using one of the c-kit mutant mouse strains, the W/W e , it was reported that the ICC-DMP, commonly considered spared by the gene mutations (24,28,35,36), lost the NK1 receptor and received a significant reduced number of SP nerve endings ( Figure 3). This result was considered responsible for an anomalous tachykinergic control of the Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 9:13 PM disorders resulted in the recovery of ICC networks suggesting the existence of ICC plasticity (18). In healthy, ICC numbers are dynamic (39) indicating that the integrity of the ICC networks has to be tightly controlled with processes that regulate both ICC loss and ICC replacement.…”
Section: Icc and Nerve Contactsmentioning
confidence: 99%
“…The CD117(c-kit)+/CD44-phenotype of cells found in the cell rich zone is suggestive for a stemness (ICCs) which are slow wave-generating cells or mediate neurotransmission [4]. ICCs are not unique to the gut and are present in other rhythmically active structures [14]. In the myenteric plexus c-kit-positive multipolar ICCs form dense networks which envelop ganglia and nerves [4].…”
Section: Discussionmentioning
confidence: 99%
“…ICC loss and injury is now a major research focus as it is recognized as a hallmark of several GI motility disorders [10], including gastroparesis [11,12], slow transit constipation [13,14] and intestinal pseudo-obstruction [15,16]. In addition, progressive depletion of ICC is known to occur as part of normal ageing [17].…”
Section: Introductionmentioning
confidence: 99%